Cianobactérias marinhas bentônicas filamentosas do litoral do Estado da Bahia, Brasil - Caires, Taiara Aguiar (2013)
(Benthic filamentous cyanobacteria from the coast of the State of Bahia, Brazil). Cyanobacteria exhibit morphological and physiological characteristics that enable them to occupy different environments, such as the marine. In these environments cyanobacteria present widely different morphologies depending on the environmental characteristics such as the type of substrate and the hydrodynamics. Despite the large expanse of coastal Brazil, this group is often excluded from floristic and ecological studies of marine communities. From Bahia, which has the longest coastline of Brazil, are listed only two benthic filamentous species, highlighting the need to conduct a survey to know the real diversity of cyanobacteria in this region. Thus, this study aims to know the biodiversity, the ecological and geographic distribution of marine benthic filamentous cyanobacteria from the coast of Bahia. We analyzed samples from 23 sites along the coastline comprising four economic macro-regions of the coast of Bahia. The samples were characterized with respect to microhabitat, habit and substrate type, in addition to frequency of occurrence. The preservation of the samples was performed in formalin (4%). Hoffmann et al. (2005) with modifications Komárek (2006) was the classification system used. The material was deposited in the Herbarium ALCB of UFBA with duplicates in the UEFS Herbarium. We identified 33 taxa belonging to 18 genera and nine families. The order Pseudanabaenales was the less diverse (5 taxa), while Oscillatoriales was the most representative (19 taxa). Nostocales was represented by nine taxa. Possibly, 10 taxa are new species and one is a new genus to science. 23 new occurrences are reported: 10 to Bahia, 11 to the Northeast region and two to Brazil. Most taxa showed rare occurrence (23 taxa), and only six species showed uncommon occurrence. Symploca cf. hydnoides was the species with the widest distribution in the coast of Bahia. The greatest diversity was observed in the protected region reef (17 taxa), followed by tide pool (11) and supralittoral (8). The epilithic habit was the most common, with 21 occurrences, followed by epiphytic, with 15. Only two species showed epizoic habit. Only Oscillatoriales occurred in all substrate types on the beaches. The more diverse macroregion was the South Coast, with 20 taxa, followed by the Metropolitan Region of Salvador, North Coast and Extreme South, with 17, 12 and 5 taxa respectively. This study can help in the development of new studies of cyanobacteria in coastal marine environment, due to the scant literature dealing on this topic. There are beaches and coastal environments subsampled in Bahia, as well as in Brazil, highlighting the need for further studies on this subject in order to demonstrate the actual biodiversity in this group on the Brazilian coast.